Deinstitutionalization - Gronfein, William (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Both the system of state hospitals which developed in the 19th century and the deinstitutionalization of the mentally ill were initially launched as reform movements, and came to be viewed as movements that had failed to deliver on their early promise. For each development (i.e., the growth of the state hospitals and the deinstitutionalization movement), discuss the following: